If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4 + -2x) = 12 (4 * 6 + -2x * 6) = 12 (24 + -12x) = 12 Solving 24 + -12x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -12x = 12 + -24 Combine like terms: 24 + -24 = 0 0 + -12x = 12 + -24 -12x = 12 + -24 Combine like terms: 12 + -24 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| 5v-4/10=8t-14 | | 13=11-1/5m | | 8(n-2)-(3-3n)=10n | | x+(2x)+(3x+30)= | | 0/7/8=0 | | 6(4-x)=18x | | 1-4p/50.2 | | 6+7[4x+8]=34 | | -3y=(4(y-1))/5 | | 17x+=20x-14 | | 16t=272 | | 5t+16=6+5w | | 12.5=2gb-3.5 | | 2/3×3/4k=71/12 | | 5.3(n-4.3)=-4.4(2.9+3.7n)+7.7 | | 17-11=2(x-2) | | 10x-3=12x+15 | | -10+5=7x-4 | | -4x^2+13=0 | | o=8m | | 69+r=108 | | 3(2x-1)=5x | | 5a+4=-2a+4.7 | | S(-19)=9 | | 275=x+x-25+(x-25)3 | | 18-9y=30 | | 90-y=212 | | x^5+6x^4y-7x^3y^2= | | s=2.1+0.6s | | 15+.50g=25+.25g | | 36=h+14 | | -4(-6x-2w+5)= |